2005
DOI: 10.1189/jlb.0205061
|View full text |Cite
|
Sign up to set email alerts
|

PK1/EG-VEGF induces monocyte differentiation and activation

Abstract: Macrophages exist as sentinels in innate immune response and react by expressing proinflammatory cytokines and up-regulating antigen-presenting and costimulatory molecules. We report a novel function for prokineticin-1 (PK1)/endocrine gland-derived vascular endothelial growth factor. Screening of murine tissue sections and cells for specific binding site leads to the identification of macrophages as an in vivo cellular target for PK1. We demonstrate PK1 induces differentiation of murine and human bone marrow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
110
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 41 publications
6
110
0
2
Order By: Relevance
“…Because prokineticins are potent chemoattractans for monocytes and macrophages both in vitro and in vivo and are able to stimulate the release of proinflammatory and proalgesic cytokines from macrophages (17)(18)(19)(20) and monocytes (28) we can further hypothesize that PK2, released at the site of inflammation, represents a component of the cytokine-chemokine loop in inflammatory pain, which is initiated by the arrival of granulocyte and maintained by the subsequent recruitment of monocytes and macrophages. Inflammatory stimuli activate the release of the cytokine G-CSF that stimulates the synthesis and release of the chemokine PK2 by neutrophils, and this chemokine, in turn, stimulates macrophage chemotaxis and cytokine release by recruited macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because prokineticins are potent chemoattractans for monocytes and macrophages both in vitro and in vivo and are able to stimulate the release of proinflammatory and proalgesic cytokines from macrophages (17)(18)(19)(20) and monocytes (28) we can further hypothesize that PK2, released at the site of inflammation, represents a component of the cytokine-chemokine loop in inflammatory pain, which is initiated by the arrival of granulocyte and maintained by the subsequent recruitment of monocytes and macrophages. Inflammatory stimuli activate the release of the cytokine G-CSF that stimulates the synthesis and release of the chemokine PK2 by neutrophils, and this chemokine, in turn, stimulates macrophage chemotaxis and cytokine release by recruited macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PKRs in primary afferent C fibers sensitizes nociceptors to thermal, mechanical, and chemical stimuli (14)(15)(16). In neutrophils, macrophages, and dendritic cells it promotes chemotaxis and cytokine release (17)(18)(19)(20), and in capillary endothelial cells it stimulates angiogenesis (21). Testis, peripheral blood leukocytes, and macrophages express two mRNA transcripts of PK2, one coding for the canonical PK2 and the other for an elongated form containing additional 21 basic amino acids between Lys-47 and Val-48 of the mature PK2 protein, named PK2L (6,19,22).…”
mentioning
confidence: 99%
“…Interestingly, PKR1 and PKR2 are most strongly expressed by Kupffer cells. Recent reports have demonstrated that PK2/Bv8 has potent cytokine properties, PK2/Bv8 has the ability to stimulate monocyte production, mobilization and differentiation into macrophage like cells [19,20] . Therefore we can speculate that, in normal liver macrophage physiology, PK2/Bv8 could act by an autocrine manner on the resident macrophage population in the liver sinusoids.…”
Section: Discussionmentioning
confidence: 99%
“…Prokineticins bioactivities includes, smooth muscle contraction in the gastrointestinal tract [14] , supporting neuronal survival, pain sensation and circadian rhythms in the central nervous system [15][16][17] . Prokineticins display also potent cytokine properties, such as inducing bone marrow leukocyte production, and modulating the growth and function of peripheral leukocytes [18][19][20] . These peptides were also shown to act as angiogenic mitogens, indeed, PK1/EG-VEGF and PK2/Bv8 induce proliferation, migration and fenestration of endothelial cells from adrenal capillaries [21,22] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation